The role of health literacy in enhancing health promotion efforts: A systematic review - Tuti Rohani (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Health literacy is one of the most important factors in improving the quality of life of the community. However, in developing countries such as Indonesia, most people have low levels of health literacy, especially in rural areas. This causes inadequate public health management, so the level of community literacy must be considered when designing health promotion programs. Purpose: To investigate the role of health literacy in enhancing health promotion efforts. Method: A systematic literature review study in the context of cervical cancer prevention promotion using techniques based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This study used the PICOS framework (Population = General, Intervention = Health promotion, Comparison = Using a comparison group and not using a comparison group, Outcome = Health Literacy, and Study Design = Various research approaches, experimental studies, mixed methods, randomized controlled trials (RCTs), longitudinal multicentric prospective intervention studies, included in the study design). Results: Health literacy plays an important role in health promotion in various countries according to the literature analyzed. The health literacy rate in China increased from 6.48% to 23.1%. The majority of university students in Portugal have limited literacy levels. According to studies conducted in South Korea and Ethiopia, there is a relationship between health information orientation and health behavior. Children and pregnant women in Lithuania and Thailand experienced significant improvements in their health competencies as a result of parental health literacy and participation in special programs. These findings highlight the importance of health literacy improvement strategies implemented at the local level. Conclusion: Health promotion programs tailored to an individual’s health literacy level have been shown to be more effective in increasing community understanding and encouraging behavior changes that support long-term well-being. Suggestion: Additional research is needed to determine the most effective strategies or approaches that can be used to address health literacy gaps across communities, especially in areas with low health literacy.